Searching Meaning of Jihad for Indonesian Muslim in the Post Reformed Era of Indonesian Polity - Rahman, Rizwanur; Hammam (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This paper aims to analyze the progressive meaning of jihad not only as religious discourses but also teachingpracticed by Indonesian Muslim from a long time ago until the reformed era. In this political transition todemocracy, Indonesian government has encountered many ideologies including transnational Islamicmovements promoting biased idea of jihad containing a lot of tension, hatred, and violence such as war,exclusive, intolerance, monolithic point of view, and single truth claim. These ideas have been extremelydifferent from Indonesian Muslim scholars and cleric thought that have interpreted jihad locally and hasbeen practiced harmoniously for a long time. Therefore identifying the concept of jihad in democratic era willbe a solution of contemporary development of Indonesian Islam and promote harmonious coexistence.Method used in this research is narrative analysis, written and spoken texts are categorized as data. Thedata focuses on the concept of jihad classified into moderate jihad and immoderate jihad as constructed byIndonesian Muslim scholars especially those affiliated with Muhammadiyah and Nahdltul Ulama (NU).This research found that jihad for Indonesian Muslim perspectives (both Muhammadiyah and NahdlatulUlama) in the post-reform era of Indonesian polity is defined as any struggle or effort made with right faithand right intention in order to strengthen the word of truth, to bring about peace, to help humanity withoutthe involvement or greed of personal gain, fame, and other fortunes continuing until the end of the day. Thisresearch contributes to the field of Islamic studies and political sociology by offering a localized perspective onjihad, distinct from Middle Eastern interpretations. It reinforces the idea that Islamization in Indonesia hashistorically been peaceful and adaptive, shaped by the nation’s socio-political context. Methodologically, thisstudy advances narrative analysis as an effective tool for examining the evolution of religious concepts andtheir implications to contemporary society.